Enrichment of amylopectin in sub-tropically adapted maize hybrids through genomics-assisted introgression of waxy1 gene encoding granule-bound starch synthase (GBSS). (May 2022) - Talukder, Zahirul A.; Muthusamy, Vignesh; Chhabra, Rashmi; Bhatt, Vinay; Reddappa, Shashidhar B.; Mishra, Subhra J.; Prakash, Nitish R.; Kasana, Ravindra; Chauhan, Hema S.; Mehta, Brijesh K.; Guleria, Satish K.; Zunjare, Rajkumar U.; et al.
Abstract: High amylopectin-based waxy maize is popular as food-, feed- and industrial products. Traditional maize is low in amylopectin (∼70–75%), while waxy maize due to the recessive waxy1 ( wx1 ) gene possesses ∼95–100% amylopectin. Here, the recessive wx1 gene was introgressed (from MGU-102- wx1 ) into three elite inbreds that are the parents of two popular sub-tropically adapted maize hybrids viz., HM4 (HKI1105 × HKI323) and HM9 (HKI1105 × HKI1128). BC1 F1, BC2 F1 and BC2 F2 populations were successfully genotyped using gene-based SSR, phi022 . The Wx1 gene segregated as per Mendelian inheritance. Background selection using 104–107 SSRs helped in recovering >94% of the recurrent parent genome. MAS-derived inbreds possessed an average of 96.7% amylopectin (range: 95.1–98.7%) compared to 70.5% (range: 69.2–71.6%) among original inbreds. The reconstituted waxy hybrids also recorded significantly higher amylopectin (mean: 98.0%, range: 96.9–98.9%) compared to original hybrids (mean: 69.7%, range: 69.1–70.2%). Waxy hybrids both in yellow and white genetic backgrounds possessed similar grain yield (mean: 5871 kg/ha, range: 5511–6295 kg/ha) with their original versions (mean: 5914 kg/ha, range: 5817–6010 kg/ha) across three locations. These waxy hybrids rich in amylopectin hold significant promise for food security and industrial use. This is the first report of conversion of normal maize hybrids to high amylopectin using genomics-assisted breeding. Graphical abstract: Image 1 Highlights: Traditional maize possesses low amylopectin thus low in food and industrial value. Recessive wx1 gene was introgressed into two popular white maize hybrids. Hybrids with wx1 possessed 98.0% amylopectin compared to 69.7% in original hybrids. Waxy hybrids had similar grain yield with their original versions. First report of development of waxy maize using genomics-assisted breeding.